Políticas pública educacionais de prevenção às drogas na tríplice fronteira Brasil-Paraguai-Argentina - Oliveira, Sergio Paulo de (2024)
Currently, drugs constitute one of the biggest challenges facing global society. The consequences of this phenomenon spread across different spheres of life. Thus, trafficking, violence, homicides, incarceration, and addiction are just some visible results of this situation. In turn, the Brazil – Paraguay – Argentina Triple Border, due to its geographic location and the intense circulation of vehicles, people, and goods, is in a situation of marked vulnerability to the consequences of this problem. In general, the main strategies for coping with drug addiction occur within the scope of repression. However, based on our vast personal experience in the area, we are fully convinced that prevention produces more effective results. Therefore, aiming to contribute to this process, this scientific investigation presents as a research problem the following question: How can the implementation of public educational policies for drug prevention jointly by the municipalities of the Triple Border contribute effectively to confronting the relative risks the initiation and dependence on psychoactive substances by children and adolescents? In the search for answers, we sought to identify and analyze public policies (actions, programs, and projects) to prevent the misuse of drugs in education implemented in the municipalities of Foz do Iguaçu-Brazil, Ciudad del Este-Paraguay, and Puerto Iguazú-Argentina. To collect this data, the main tool used is field research. Therefore, a semi-structured interview was carried out with managers and executors of these public policies. In this light, it should be noted that this research is characterized as qualitative in terms of approach, descriptive according to its nature and bibliographical, documentary and fieldwork in terms of procedures. In the analysis and interpretation of the data, the Content Analyses is used. It should be emphasized that Bardin (2016), Yin (2016), Flick (2004) and Creswell (2007; 2014) are the authors most used to interpret the collected material. Furthermore, in this analysis process, the IRAMUTEQ software is used. At the end of all stages of the work, some proposals for educational public policies for drug prevention are drawn up that can be adopted jointly by the three municipalities that make up this territory full of beauty and possibilities and, paradoxically, risks and challenges. The definitive product of this study will be made available to public managers in related areas in the three municipalities, in the three countries.